Nuclear hormone receptors as mediators of metabolic adaptability following reproductive perturbations. Issue 1 (2nd January 2016) - Ratnappan, Ramesh; Ward, Jordan D.; Yamamoto, Keith R.; Ghazi, Arjumand
ABSTRACT: Previously, we identified a group of nuclear hormone receptors (NHRs) that promote longevity in the nematode Caenorhabditis elegans following germline-stem cell (GSC) loss. This group included NHR-49, the worm protein that performs functions similar to vertebrate PPARα, a key regulator of lipid metabolism. We showed that NHR-49/PPARα enhances mitochondrial β-oxidation and fatty acid desaturation upon germline removal, and through the coordinated enhancement of these processes allows the animal to retain lipid homeostasis and undergo lifespan extension. NHR-49/PPARα expression is elevated in GSC-ablated animals, in part, by DAF-16/FOXO3A and TCER-1/TCERG1, two other conserved, pro-longevity transcriptional regulators that are essential for germline-less longevity. In exploring the roles of the other pro-longevity NHRs, we discovered that one of them, NHR-71/HNF4, physically interacted with NHR-49/PPARα. NHR-71/HNF4 did not have a broad impact on the expression of β-oxidation and desaturation targets of NHR-49/PPARα. But, both NHR-49/PPARα and NHR-71/HNF4 were essential for the increased expression of DAF-16/FOXO3A- and TCER-1/TCERG1-downstream target genes. In addition, nhr-49 inactivation caused a striking membrane localization of KRI-1, the only known common upstream regulator of DAF-16/FOXO3A and TCER-1/TCERG1, suggesting that it may operate in a positive feedback loop to potentiate the activity of this pathway. These data underscore how selective interactions between NHRs that function as nodes in metabolic networks, confer functional specificity in response to different physiological stimuli.